On the cauchy problem for a one‐dimensional full compressible non‐Newtonian fluids. (4th November 2015) - Liu, Xin; Qin, Yuming
Abstract : This paper is concerned with global existence and asymptotic behavior of H 1 solutions to the Cauchy problem of one‐dimensional full non‐Newtonian fluids with the weighted small initial data. We then obtain the global existence of H i ( i = 2, 4) solutions and their asymptotic behavior for the system. Copyright © 2015 John Wiley & Sons, Ltd.